Penerapan Arsitektur Metafora pada Strategi Perancangan Pusat Kecantikan Tradisional di Surakarta - Dyah Permatahati, Raras Sekarwangi; Sumaryoto, Sumaryoto; Purnomo, Agus Heru (Universitas Sebelas Maret Surakarta, 2019)
Public request for beauty care services continues to increase. The production of cosmetics and beauty clinics are also increasing at the same time. Some cosmetics that contain hazardous substances on the market make consumers more smart to choose non-hazardous ones by using natural cosmetics. Traditional beauty centers in Surakarta aim to realize the provision of traditional beauty treatments with natural ingredients as well as providing facilities for relaxation, education, and art and gallery as complementary facilities. The main problem of this building design is how to attract visitors and show them that it’s a commercial building that accommodates beauty activities using a metaphorical architectural approach. The result of the design is Traditional Beauty Center in Surakarta that can attract attention and bring visitors. Public can see that this is Traditional Beauty Center just to see through the building. To obtain the criteria, the method that will be used are observational studies to the community, field studies, and literature studies on related theories.